EFFICACY OF DIFFERENT TACTICS FOR INITIAL ANTIHYPERTENSIVE THERAPY - O. A. Pleyko; A. O. Konrady (Столичная издательская компания, 2015)
Aim. To evaluate different tactics of initial antihypertensive therapy. Material and Methods. 120 patients with mild-to-moderate arterial hypertension were included and randomized into three groups: "A", "B", and "C". 5 drugs from the main antihypertensive classes were used: indapamide, bisoprolol, amlodipine, fosinopril, and rilmenidine as well as fixed drug combination of fosinopril and hydrochlorothiazide. Patients included in group "A" received initial therapy according to individual leading pathogenic variant of hypertension. Patients from group "B" received standard stepped antihypertensive therapy with gradual dose increase and further addition of second (third) drug. Patients in group "C" were immediately administrated fixed drug combination and later added other drugs. Visits were scheduled after 2, 4, 6, 8, 10, etc weeks of treatment up to achievement of target blood pressure (BP). Results. In group "A" 33 patients (82,5%) achieved target BP after 6 visits, in group "B" - 37 patients (92,5%) after 8 visits and in group "C" - 100% of patents after 6 visits. Thus, in group "C" there was less number of visits and respectively lower number of therapy changes in order to achieve target BP. No significant discrepancies between group "A" and "B" were observed. Conclusion. Tactics of initial antihypertensive therapy with usage of fixed drug combination results in more effective and fast achievement of target BP.